Effectiveness of neoton in patients with heart failure receiving sacubitril/valsartan. Sub-analysis of the BYHEART study - S. N. Tereshchenko; A. A. Safiullina (Российский кардиологический журнал)
Aim. To study the effectiveness of exogenous phosphocreatine (EP) therapy in patients with heart failure (HF) with reduced and mildly reduced ejection fraction (EF) receiving sacubitril/valsartan.Material and methods. The nationwide prospective observational study BYHEART included a total of 842 patients who underwent intravenous EP therapy. To achieve this goal, a group of patients was identified that received sacubitril/valsartan (n=139). Before and after the EP course, the following methods were used: the Minnesota Living with Heart Failure Questionnaire (MLHFQ), Rating Scale of Clinical State, transthoracic echocardiography assessing left ventricular EF (LVEF), 6-minute walk test (6MWT), assessment of NT-proBNP level.Results. Of the 139 patients included in the study, 69,06% (n=96) were male. The mean age was 62,89±12,2 years. Of the entire cohort of patients with HF, 50 patients had class II (35,97%), 80 — class III (57,56%), 9 — class IV (6,47%). EP therapy led to a significant improvement in the quality of life (from 67±17 to 49±16, p<0,01, delta -6,7), a decrease in the Rating Scale of Clinical State score (from 7,7±2,8 to 5,6±2,1, p<0,01, delta -2,2), an increase in 6MWT distance (from 261±85 m to 310±74 m, p<0,01, delta 49 m), LVEF (from 38,5±7,01% to 40,25±6,58%, p<0,01, delta 1,75%), decreased NT-proBNP concentration (from 1000 [602; 1869] pg/ml to 832 [469; 1614] pg/ml, p<0,01).Conclusion. The results obtained demonstrate that adjuvant intravenous mitochondrial EP therapy in patients with HF receiving sacubitril/valsartan improves quality of life, decrease the Rating Scale of Clinical State score and NT-proBNP concentration, as well as increase 6MWT distance and LVEF.